Effect of occupational noise exposure on cortisol hormone level: A systematic review. (December 2022) - Naderyan Fe'li, Shadi; Monazzam Esmaielpour, Mohammad Reza; Hokmabadi, Rajabali; Rezaei-Hachesu, Vida
Introduction. The aim of this review was to investigate the possible association between noise exposure and cortisol hormone in all noise-exposed job classifications.Materials and methods. In this systematic review, the Medline (PubMed), Scopus, Web of Science, and Embase databases were searched from 1 January 1991 to 28 September 2021. As a result, all English relevant papers among any group of workers, in any workplace, and at any noise level were included. Abstracts without full texts, editorials, letters, case reports, conference proceedings, reviews, in-vitro, and animal studies were excluded. Furthermore, studies were removed in the case that they were conducted on children or general population, did not measure the noise levels in work environments, and simulated the workplace noise or used a noise chamber.Results. The initial search retrieved 5784 articles. Finally, 13 articles were considered for qualitative synthesis. Among all the included studies, most of them (10 vs. three), conducted in various industries reported a statistically significant association between occupational noise exposure and increased levels of cortisol hormone.Conclusion. Our qualitative synthesis of available evidence proposed a potential relationship between occupational noise exposure and cortisol hormone. So, noise can be considered an occupational health concern.